Dual effects of cyclic ADP-ribose on sarcoplasmic reticulum Ca2+ release and storage in cardiac myocytes isolated from guinea-pig and rat ventricle. - Macgregor, A; Rakovic, S; Galione, A; Terrar, D (2007)
The actions of cyclic ADP-ribose (cADPR), a regulator of Ca2+-induced Ca2+ release (CICR), were investigated on Ca2+ release and sarcoplasmic reticulum (SR) Ca2+ loading in cardiac myocytes at physiological temperature. In guinea-pig ventricular cells, cADPR, applied via patch pipette or from photorelease of its caged derivative, increased contraction amplitude and whole-cell Ca2+ transients, without affecting SR Ca2+ load (measured in response to rapid caffeine application). Under voltage-clamp conditions, photorelease of caged cADPR enhanced Ca2+ transient magnitude without affecting the peak amplitude of L-type Ca2+ current or its rate of decay, indicative of an increase in CICR gain. In rat permeabilised ventricular myocytes, rapid application of cADPR increased Ca2+ spark frequency within 30 s, and this effect was maintained over a 10 min exposure. Enhancement of spark frequency was not associated with changes in SR Ca2+ load at 30 s and 3 min of exposure to cADPR; however, prolonged exposure (10 min) was associated with an increased SR Ca2+ load (32+/-7%). The observations are consistent with dual actions of cADPR: a rapid effect on CICR that does not depend on an increased SR Ca2+ load, and an additional slower effect that is associated with enhanced SR Ca2+ levels.